PENGARUH AI (CHAT GPT) GENERATIF TERHADAP ETIKA DAN MINAT BELAJAR SISWA SMA KOTA PADANG - Putri Sarah, Ririn Amaliah; Merdila Nuril Fahmi; Fadli Ilham; Nurkemala Sari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the influence of generative AI such as ChatGPT on academic ethics and learning interest among high school students in Padang City. The use of AI in education is increasing, but there are concerns about its impact on academic integrity and student motivation. This study uses a quantitative approach with a survey method involving 150 students from five high schools in Padang City. The results show that ChatGPT usage is high with a score of 4.12, learning interest is also high with a score of 4.01, but academic ethics is only moderate with a score of 3.45. This indicates that while ChatGPT aids in understanding course material, it also poses challenges in maintaining academic integrity. This study offers an ethical framework for the use of AI in school environments to optimize benefits and minimize negative impacts.